Pengaruh Kreativitas dan Pembelajaran Kewirausahaan Terhadap Minat Berwirausaha Siswa SMAN 1 Sungai Rumbai - Anggun Fitri; Armiati Armiati (Jurnal Salingka Nagari, 2024)
The purpose of this study is to analyze 1) the effect of creativity and entrepreneurial learning on students' enterpreneurial interest at SMAN 1 Sungai Rumbai, 2) the effect of creativity on students' enterpreneurial interest at SMAN 1 Sungai Rumbai, and 3) the effect of entrepreneurship learning on students' enterpreneurial interest at SMAN 1 Sungai Rumbai. This study's population consisted of students from classes X, XI, and XII. The Slovin formula was used to select 230 students for the study, and the proportionate stratified random sampling technique was used. The data is classified as primary data. Multiple linear regression is a data analysis technique used in research. The findings of this study, (1) Creativity and Entrepreneurship Learning have a significant effect on students' interest in entrepreneurship at SMAN 1 Sungai Rumbai, (2) Creativity has a significant effect on students' enterpreneurial interest at SMAN 1 Sungai Rumbai, and (3) Entrepreneurship Learning has a significant effect on students' entrepreneurship at SMAN 1 Sungai Rumbai.